Total mercury and methylmercury in rice: Exposure and health implications in Bangladesh. (October 2020) - Wang, Yajie; Habibullah-Al-Mamun, Md; Han, Jialiang; Wang, Le; Zhu, Yaru; Xu, Xiaohang; Li, Ning; Qiu, Guangle
Abstract: Rice methylmercury (MeHg) contamination has attracted global attention, especially in countries where rice is considered a staple food. The daily rice intake rate in Bangladesh ranks first in the world; however, no attention has been paid to rice MeHg contamination in Bangladesh. Total Hg (THg) and MeHg concentrations of commercial rice (n = 172) from Bangladesh were first analyzed to accurately evaluate both rice MeHg and inorganic Hg (IHg) exposure in different age-gender groups of Bangladeshis. The corresponding adverse health impacts and associated economic loss were also assessed. The results showed that THg concentration in all samples ranged from 0.42 to 14.4 ng/g, with an average of 2.48 ± 1.41 ng/g, while the MeHg concentration ranged from 0.026 to 7.47 ng/g, with an average of 0.83 ± 0.60 ng/g. The highest average MeHg and IHg were both recorded in rice from Chittagong. The highest mean MeHg and IHg exposures were observed in 2–5 years-old group and were 16.2% of the reference dose (RfD) of 0.1 μg/kg/day for MeHg and 7.09% of the provisional tolerable weekly intake (PTWI) of 0.571 μg/kg/day for IHg. Surprisingly, MeHg exposure of the 2-5 year-old children could be up to 93.7% of the RfD at a high percentile (P99.9). The total intelligence quotient reduction caused by rice MeHg exposure could be 54700 points, and the associated economic loss is approximately 42.5 million USD. To avoid high rice MeHg exposure, it was suggested that diet structure be improved. More attention should be paid to residents with long-term rice MeHg exposure, especially children in the 2-5 year-old group. Graphical abstract: Image 1 Highlights: We first conducted a nationwide investigation of Hg in Bangladeshi commercial rice. Although low Hg in rice, high Hg exposure could be caused by high rice intake rate. Rice MeHg exposure to 2–5 years old group can be 93.7% of the RfD-0.1 μg/kg/day. Rice MeHg exposure to human may impact human health and economy in Bangladesh. Abstract : Capsule: Due to their rice intake rate, which is the highest in the world, 2-5 year-old Bangladeshis may be exposed to MeHg levels higher than the MeHg reference dose of 0.1 μg/kg/day.